Monitoring Indoor Air Quality and Occupancy with an IoT System: Evaluation in a Classroom Environment - Ramos, A. (2023)
Indoor air quality is a determining factor in maintaining occupant comfort, especially in educational environments such as classrooms. Traditional methods of monitoring indoor air quality and occupancy, such as casual inspections or periodic measurements, do not provide timely and accurate information for those who must make decisions about ventilation and controlling the number of occupants. Internet of Things (IoT) technology has opened new possibilities for monitoring and controlling indoor air quality in real time. In this paper, an IoT-based system for monitoring indoor air quality and occupancy in a classroom is presented. The system consists of low-cost sensors that collect data on temperature, humidity, dust, carbon dioxide levels and occupancy, which is then transmitted to a cloud-based platform for analysis and visualization. Evaluation of the system in a real-world classroom environment has shown its effectiveness in detecting changes in air quality and the number of occupants.